The Effectiveness of Adaptive Learning Systems Integrated with LMS in Higher Education - andhika, Andhika; Aldila, Amalia Shifa; Supriyono, Lawrence Adi; Previana, Cantika Nur; Habibie, Dedi Rahman (Universitas Putra Indonesia YPTK Padang, 2024)
Higher education has been paying close attention to adaptive learning systems (ALS) coupled with learning management systems (LMS) because of their potential to improve student outcomes and personalise learning experiences. The purpose of this study is to assess how well ALS combined with LMS can raise student engagement, academic achievement, and general satisfaction in higher education environments. Using a combination of quantitative data from academic performance measurements and qualitative input from focus groups and student questionnaires, a mixed-methods approach was used. A mid-sized university hosted the study over two semesters, with 500 undergraduate students enrolled in a range of subjects. A control group utilising a conventional LMS and an experimental group using an LMS linked with ALS were each given a set of participants. The quantitative analysis revealed a statistically significant improvement in academic performance for students in the experimental group (p < 0.05). Additionally, student engagement, measured through LMS activity logs and interaction frequencies, was notably higher in the experimental group. Qualitative feedback indicated that students appreciated the personalised learning paths and timely feedback provided by the ALS, reporting increased motivation and satisfaction with their learning experience. The integration of adaptive learning systems within LMS platforms demonstrates a positive impact on student academic performance, engagement, and satisfaction in higher education. These findings suggest that educational institutions should consider adopting an ALS-integrated LMS to support personalised learning and improve educational outcomes. Further research is recommended to explore the long-term effects and scalability of such systems across diverse educational contexts.